2016
DOI: 10.1007/s11595-016-1373-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the residual strength for durability failure of concrete structure in acidic environments

Abstract: According to the results of accelerated tests of acidification corrosion depth and compressive strength of concretes subjected to sulfuric acid environments, the acidification depth laws of concretes were predicted based on the grey system theory. Thus, the remaining compressive strength was calculated when the acidification depth reached the protection layer thickness of concrete structures, which indicates that the limit state of durability failure can be defined based on strength degradation, and the calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…The average final estimates of parameters 𝑓 𝑐,𝑊 ′ and 𝑓 𝑐,𝐸 ′ are approximately 30% and 26% less than their initial values. Previous studies [63,64] have shown more than 25% reductions in concrete compressive strength of deteriorated concrete structures-e.g., abandoned structures and structures in acidic environments. Considering that the operating environment of girders caused them to be prone to various damage mechanisms (including concrete degradation, as well as steel corrosion as discussed in Section 2.1) the final estimates of parameters 𝑓 𝑐,𝑊 ′ and 𝑓 𝑐,𝐸 ′ are reasonable.…”
Section: Resultsmentioning
confidence: 98%
“…The average final estimates of parameters 𝑓 𝑐,𝑊 ′ and 𝑓 𝑐,𝐸 ′ are approximately 30% and 26% less than their initial values. Previous studies [63,64] have shown more than 25% reductions in concrete compressive strength of deteriorated concrete structures-e.g., abandoned structures and structures in acidic environments. Considering that the operating environment of girders caused them to be prone to various damage mechanisms (including concrete degradation, as well as steel corrosion as discussed in Section 2.1) the final estimates of parameters 𝑓 𝑐,𝑊 ′ and 𝑓 𝑐,𝐸 ′ are reasonable.…”
Section: Resultsmentioning
confidence: 98%
“…However, due to the shortage of wood resources and fire safety considerations, the government set strict rules to limit the use of timber and more attention was paid on the study and construction of steel and concrete a The Glulam Beam is locally manufactured by YF, its elasticity modulus is obtained based on their tested results. structures (Li et al, 2016;Karol et al, 2018;Li and Wang, 2021). Thus, the timber construction decreased rapidly and there have height and area limitations on it (timber structures were once limited to no more than three storeys in China, and the height was limited to no more than 10 m) (GB50016-2014: Code for Building Ddesign on Ffire protection, 2018).…”
Section: Timber Construction In Chinamentioning
confidence: 99%
“…a) Incomplete element information, b) incomplete structural information, c) incomplete boundary information, and d) incomplete operational behavior information [18]. Gray system theory uses the gray system method and modeling technology, through the analysis of a small amount of "known information", to identify the key information and relationships in the system and to predict the future development trend of the system [19,20]. GM has differences and compatibility, GM structure has elasticity and diversity, GM is a constant coefficient in nature, and its parameter distribution is gray [21].…”
Section: Introductionmentioning
confidence: 99%